Mapping whole brain structure and activity at cellular resolution: iDISCO+ and ClearMap - Kirst, Christoph (J Biomol Tech, 2020)
Understanding how neural information is processed or brain structures are altered in physiological and pathological states would benefit from precise detection, localization, and quantification of cells across the entire brain. Here we introduce a pipeline for high-speed acquisition of brain structure and activity at cellular resolution based on iDISCO tissue clearing combined with immunostaining, light-sheet fluorescence imaging, and automated mapping and analysis via an open-source software program, we term ClearMap [1-3]. We apply our pipeline to map neuronal activity via immediate early gene expression and validate our method by analysis of brain regions activated in response to the drug haloperidol [1]. We combine activity mapping with axon tracing to uncover new brain regions differentially activated during parenting behavior [1]. Finally, we use our pipeline to map the entire vasculature network of a mouse brain at capillary resolution [2]. This pipeline is widely applicable to different experimental paradigms, including animal species for which transgenic activity reporters are not readily available. [1] Renier*, Adams*, Kirst*, Wu*, et al., Cell 2016 [2] Kirst et al., accepted, Cell 2020 [3] https://idisco.info